Kunst Heute in Ungarn. - Alexa, Karoly; Andrási, Gabor; Aszalos, Endre; Becker, Wolfgang; Beke, László; Bereczky, Lorand; Birkás, Ákos; Csorba, Geza; Devenyi, Istvan; F., Laszlo Földenyi; Ferenc, Hann; Frank, Janos; et al. (Aachen : Neue Galerie - Sammlung Ludwig Aachen, 1989)
Bak, Imre ; Bakos, Ildiko ; Bartl, Jozsef ; Berczeller, Rudolf ; Birkás, Ákos ; Bohus, Zoltan ; Bukta, Imre ; Cseszlai, György ; Csiky, Tibor ; Deim, Pal ; Feher, Laszlo ; Földi, Peter ; Föth, Erno ; Gabor, Aron ; Gyemant, Laszlo ; Jovanovics, Gyorgy ; Jovian, György ; Karolyi, Zsigmond ; Kelemen, Karoly ; Keserü, Ilona ; Klimo, Karoly ; Kocsis, Imre ; Koka, Ferenc ; Kokas, Ignac ; Kovacs, Peter ; Lorant, Janos ; Lugossy, Lászlo fe ; Lugossy, Maria ; Mata, Attila ; Mazzag, István ; Mulasics, Laszlo ; Nadler, Istvan ; Nagy, Gabor ; Paizs, Laszlo ; Pinczehelyi, Sandor ; Samu, Géza ; Soos, Tamas ; Szabados, Arpad ; Szirtes, János ; Török, Richard ; Ujhazi, Peter ; Varga, Imre ; Várnagy, Ildikó ; Wahorn, Andras ; Zaborszky, Gabor ; Zambo, Istvan Ef
biografie, bibliografie
Kunst Heute in Ungarn, Neue Galerie - Sammlung Ludwig Aachen, 10.2.1989 - 16.4.1989 mit unterstützung der Ludwig Stiftung für Kunst und Internationale Verständigung
Duits
boek
Keywords: Hongarije